The practice of interdisciplinarity in Technological Education projects - Cardoso, Ana Paula (2017)
The rapid development of technology, together with the expertise of scientific knowledge requires a change in teaching-learning methodologies in schools in order to contribute to the integration of knowledge. In the discipline of Technological Education (TE) it is customary to turn to implementing interdisciplinary practices based on project-based methodologies. Promoting the value of these practices means relying on more innovative education, dedicated to developing individuals who are flexible, critical, supportive and receptive to change in response to the demands of a society in constant transformation. To that end, we sought to discover the perception teachers, students and employers in the local community have with regards to the importance of interdisciplinarity in developing TE projects. For this, a descriptive and exploratory study was conducted based on a survey questionnaire and interview. The convenience sample consisted of 11 TE teachers, mostly female, aged between 50 and 59 years; 987 students of both sexes, aged 12 or older, attending the 3rd cycle of basic education [7th – 9th years of schooling]; and 15 representatives of employers, mostly male, taking place in four school groupings in the central region of Portugal. The data indicate that most teachers consider it very important to articulate TE with the other disciplines of the academic year, with an identical the percentage for those admitting they put it into practice a few times and those who say that they always or almost always do. They mention the transfer of scientific knowledge from one domain to another as the main advantage. Regarding students, they consider that a TE project is more interesting when it is carried out in connection with other disciplines in the same academic year and that it should favour the use of devices and the interaction between knowledge. As for employers, they are unanimous in affirming the importance of schools promoting interdisciplinary projects and all consider it relevant that schools establish regular partnerships with local community organizations. These data reinforce the importance of schools, and TE teachers in particular, in promoting interdisciplinarity together with the professional context, since this is an asset not only from the curricular standpoint, but also to train autonomous citizens who participate in community life.